Malignant peripheral nerve sheath tumor in early childhood: a case report of a diagnostic challenge - Zhang, Xin; Guan, Wenbin; Liang, Jianqing (Frontiers in Oncology, 2025)
BackgroundMalignant peripheral nerve sheath tumors (MPNST) are a severe complication of neurofibromatosis type 1 (NF1). The median age at diagnosis is 47.1 years in the general population, whereas NF1-associated cases present significantly earlier, at 33.9 years. The incidence is 1.46 per million in the general population and 0.56 per million in children, with a higher occurrence in late adolescence.Case reportA 3-year-old girl was referred for a recurrent soft-tissue mass in her left wrist. Imaging suggested a neurofibroma. After excision, pathological analysis and genetic testing revealed a germline NF1 mutation, confirming Neurofibromatosis type 1 (NF1), along with somatic mutations in NF1 and deletions in CDKN2A. Pathology confirmed malignant Triton tumor (MTT). She received six cycles of ifosfamide and doxorubicin, followed by a second excision, which showed persistent tumor activity. Positron emission tomography–computed tomography (PET-CT) scans revealed reduced metabolic activity at the tumor site, suggesting a partial response to treatment. The patient is currently undergoing oral MEK inhibitor-targeted therapy.ConclusionThis case highlights the challenges associated with MPNST in pediatric NF1. Both surgery and chemotherapy have been shown to enhance outcomes. Ongoing monitoring is crucial, and additional research on MEK inhibitors and genetic profiling is imperative for tailoring treatment strategies.